2020
DOI: 10.3390/ani10071233
|View full text |Cite
|
Sign up to set email alerts
|

Milk Replacer Supplementation with Docosahexaenoic Acid from Microalgae Does Not Affect Growth and Immune Status in Goat Kids

Abstract: Consumption of polyunsaturated fatty acids (PUFA), especially docosahexaenoic acid (DHA), has beneficial effects for consumers’ health. Consequently, there is an increased interest in enhancing meat fatty acid profiles (i.e., PUFA and DHA content) through diverse nutritional strategies. This study aimed to investigate the effect of supplementing a microalgae-derived product rich in DHA on growth and immune system development in newborn goat kids. In this experiment, newborn goat kids were fed milk replacer (MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(74 reference statements)
1
0
0
Order By: Relevance
“…In this study, a high-fat concentrate containing DHA and EPA had no significant effect on immunoglobulin in the colostrum of ewes. This result aligns with another study that reported that feeding EPA and DHA has no significant effect on lambs' colostral IgG and serum IgG concentration (Moreno-Indias et al 2020). Colostrum synthesis depends on the diet consumed by Ewe during gestation (Banchero et al 2015).…”
Section: Resultssupporting
confidence: 91%
“…In this study, a high-fat concentrate containing DHA and EPA had no significant effect on immunoglobulin in the colostrum of ewes. This result aligns with another study that reported that feeding EPA and DHA has no significant effect on lambs' colostral IgG and serum IgG concentration (Moreno-Indias et al 2020). Colostrum synthesis depends on the diet consumed by Ewe during gestation (Banchero et al 2015).…”
Section: Resultssupporting
confidence: 91%